The norm of reciprocity enhances tax compliance : experimental evidence - Toh, Christine (2017)
The failure to file an income tax return is a significant issue in tax non-compliance. Non-filing is, however, seldom investigated in the literature because of its unobservable nature. Researchers face difficulty in obtaining observational data or running field experiments to examine the filing compliance decision. This research uses laboratory experiments to test the effect of a reciprocity message on voluntary filing compliance. The norm of reciprocity states that people would feel obliged to those who have previously helped them. Our experiments replicate income tax reporting procedures—participants can earn income and choose whether to file a tax return. Conditional on filing a tax form, participants then decide how much income to report. During the sessions, all subjects were provided with refreshments. In the treatment group, reciprocity was prompted by calling attention to this provision of refreshments. Subjects who read the reciprocity message were substantially more likely to declare their income. Our results provide evidence for the use of a reciprocity message to enhance voluntary filing compliance.